Hubungan Kebiasaan Sarapan Pagi dan Status Gizi dengan Prestasi Belajar Murid SD Negeri 1 Lelamo Kabupaten Buton Utara - Gani, Kameriah; erwin, Andi; Serni, Serni (Jurnal Gizi Ilmiah, 2017)
Ages 6 - 12 years (school age children) have a lot to do with their eating habits. Breakfast is highly recommended for school children so that when they receive lessons (1-2 hours after eating) blood sugar rises and can be used as a source of brain energy. One of the efforts to improve health is improving nutrition, especially at school age, especially aged 6-10 years. Breakfast or breakfast is an activity to eat food that contains balanced nutrition and fulfills 20% - 25% of total energy needs in the day before learning activities at school. This research is a descriptive analytic study with a cross sectional study approach. This research was conducted on 27 July – 1 August 2015 at SDN 1 Lelamo, North Buton Regency. The sample used in this study were 60 people. Breakfast habits of students by way of recall for 1 week, Determination of student achievement by looking at report cards (Indonesian, Science and Mathematics), and Nutritional Status by weighing and measuring height. The sampling technique used is purposive sampling, while the test used is the Fisher's Exact Test. This study shows that most of the 95% of respondents' nutritional status is in the normal category, 91.7% of respondents' breakfast habits are in the unusual category, 78, 3% learning achievement is in the good category. There is no relationship between breakfast habits with learning achievement and there is no relationship between nutritional status and learning achievement. This study suggests that schools can provide nutrition education to students through mulok subjects so that students can know the importance of breakfast